Comparison of drug survival on adalimumab, etanercept, golimumab and infliximab in patients with axial spondyloarthritis - Hebeisen, Monika (PLoS One, 2019)
OBJECTIVES: To compare drug survival in patients with axial spondyloarthritis treated with different TNF inhibitors in standard dosage. METHODS: Patients fulfilling the Assessment in SpondyloArthritis international Society classification criteria for axial spondyloarthritis in the Swiss Clinical Quality Management cohort were included in this study if a first TNF inhibitor on standard dosage was started after recruitment and if a baseline visit was available. Drug maintenance up to drug discontinuation or dose escalation was compared between TNF inhibitors with multiple adjusted Cox proportional hazards models and multiple imputation for missing baseline covariate data. RESULTS: A total of 966 patients were included (adalimumab 344, etanercept 237, golimumab 214, infliximab 171). Patients on certolizumab (n = 18) were excluded. Patients starting golimumab had lower disease activity as well as better physical function and quality of life in comparison to patients starting another drug. A higher proportion of patients starting infliximab had a history of extra-articular manifestations. Drug dosage was more often escalated during follow-up in patients treated with infliximab than with subcutaneously administered agents. However, no significant differences in time up to drug discontinuation or dose escalation were observed in multiple adjusted analyses if treatment was initiated after 2009, when all 4 TNF inhibitors were available: hazard ratio for infliximab versus etanercept 1.16 (95% confidence interval 0.80; 1.67), p = 0.44, for golimumab versus etanercept 0.80 (0.58; 1.10), p = 0.17 and for adalimumab versus etanercept 0.93 (0.69; 1.26), p = 0.66. CONCLUSION: In axial spondyloarthritis, drug survival with standard doses of different TNF inhibitors is comparable.